2001
DOI: 10.1001/archpsyc.58.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Volumes of Brain Structures in Twins Discordant for Schizophrenia

Abstract: Smaller intracranial volumes in the monozygotic patients and their cotwins suggest that increased genetic risk to develop schizophrenia is related to reduced brain growth early in life. The additional reduction in whole-brain volume found in the patients suggests that the manifestation of the disorder is related to (neurodegenerative) processes that are most likely nongenetic in origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
4
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(137 citation statements)
references
References 31 publications
10
121
4
2
Order By: Relevance
“…People at high risk of psychosis show qualitatively similar volumetric abnormalities to patients with schizophrenia. Cortical brain abnormalities have been found in genetically defined high-risk populations such as first-degree relatives and co-twins of patients with schizophrenia, as well in people with ARMS [13,[68][69][70][71][72][73][74][75][76][77][78][79][80]. Previous longitudinal MRI studies in this group found that the subset of patients who developed psychosis showed a longitudinal reduction in GM in the orbito-frontal, temporal lobe, parietal lobe and cerebellum [79,81,82].…”
Section: Effects Of Antipsychotic Medication On Structural Neuroimagimentioning
confidence: 83%
“…People at high risk of psychosis show qualitatively similar volumetric abnormalities to patients with schizophrenia. Cortical brain abnormalities have been found in genetically defined high-risk populations such as first-degree relatives and co-twins of patients with schizophrenia, as well in people with ARMS [13,[68][69][70][71][72][73][74][75][76][77][78][79][80]. Previous longitudinal MRI studies in this group found that the subset of patients who developed psychosis showed a longitudinal reduction in GM in the orbito-frontal, temporal lobe, parietal lobe and cerebellum [79,81,82].…”
Section: Effects Of Antipsychotic Medication On Structural Neuroimagimentioning
confidence: 83%
“…13 In terms of brain structure, brain volume is highly heritable, 14 and neocortical gray matter volumes are heritable and correlate with multiple cognitive domains; 15 hippocampal, neocortical and cortical volume deficits have also been observed to be related to genetic risk for schizophrenia in family-based studies. 5,[16][17][18] Thus, for many biological changes related to brain function and structure that are associated with schizophrenia and with increased genetic risk for schizophrenia, the evidence for their heritability is strong. In a family study of the association of a promising schizophrenia susceptibility gene, DISC1, with P300 waveforms, almost every subject with a structural abnormality in the DISC1 gene had an abnormal P300 response, even if they had no psychiatric diagnosis.…”
Section: Are So-called Intermediate Phenotypes Heritable?mentioning
confidence: 99%
“…Volumetric abnormalities in various brain areas have been reported in the non-psychotic first-degree relatives of schizophrenia patients (25)(26)(27), but there have been relatively few studies of basal ganglia structure in this population. Reduced volume of the right putamen has been reported in the unaffected siblings of subjects with schizophrenia (28).…”
mentioning
confidence: 99%